Heat transfer augmentation in a helical-ribbed tube with double twisted tape inserts - Promvonge, Pongjet; Pethkool, Somsak; Pimsarn, Monsak; Thianpong, Chinaruk (My University, 2012)
Turbulent convective heat transfer characteristics in a helical-ribbed tube fitted with twin twisted tapes have been investigated experimentally. The experiment was carried out in a double tube heat exchanger using the helical-ribbed tube having a single rib-height to tube-diameter ratio, e/D H=0.06 and rib-pitch to diameter ratio, P/D H=0.27 as the tested section. The insertion of the double twisted tapes with twist ratio, Y, in the range of 2.17 to 9.39 is to create vortex flows inside the tube. The inserted ribbed tube is arranged in similar directions of the helical swirl of the twisted tape and the helical rib motion of the tube (called co-swirl). Effects of the co-swirl motion of the ribbed tube and the double twisted tapes with various twist ratios on heat transfer and friction characteristics are examined. The results obtained from the ribbed tube and the twin twisted tape insert are compared with those from the smooth tube and the ribbed tube acting alone. The experimental results reveal that the co-swirling inserted tube performs much better than the ribbed/smooth tube alone at a similar operating condition. The co-swirl tube at Y≈8 yields the highest thermal performance at lower Reynolds number (Re). In addition, the correlations of Nusselt number and friction factor as functions of Re, Pr and Y are also proposed. © 2012 Elsevier Ltd.
Keywords: Compound heat transfer; Friction factor; Helical-ribbed tube; Swirl flow; Twisted tape